Nilai Ketuhanan Hindu dalam Sarana Upacara Bale Gading - Aryana, I Made Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The implementation of religious ceremonies in Hinduism uses certain ceremonial facilities and specifically at the ceremony. Likewise, in a potong gigi ceremony using a very striking and absolutely necessary means, namely the Bale Gading facilities/uperengga. To get information about the use of bale gading facilities in potong gigi ceremonies, information was collected using interview techniques, observation techniques, library techniques and documentation. The data obtained is of a raw nature, processed using data analysis techniques. Bale gading is a mandatory tool used in cutting teeth ceremonies. Bale Gading in the form of a small gedong (house) made of materials, supplies and decorations in gading color (yellowish-white). The material used is gading bamboo, the roof is made of braided frangipani flowers, cempaka or gumitir flowers, and the decoration uses white and yellow fabrics. The use of bale gading facilities in a potong gigi ceremony is symbolic of Sang Hyang Semara Ratih’s stance being requested and his gift during a potong gigi ceremony. In the facilities of bale gading placed upakara/banten peras ajuman daksina, canang burat wangi, canangsari completed with klungah of gading coconut which is kasturi (cut) and drawn by Semara Ratih, covered with white or yellow cloth, sangku contains water and flowers and white yellow rantasan. Bale gading is God’s sthana in manifestation of Him as Sang Hyang Semara Ratih and was asked for His grace to give the power of holy love to humanity (adolescents) to a higher level of life. In bale gading there is a function of Hinduism education, social functions and aesthetic functions.